Transmisibilidad e inocuidad de un candidato vacunal contra la tuberculosis bovina y evaluación de técnicas complementarias para el diagnóstico diferencial en la infección natural - Ferrara Muñiz, Ximena (2023)
Bovine tuberculosis (BTB), distributed worldwide, represents a problem for the\nlivestock sector and a Public Health concern due to its zoonotic nature. The main\ncausative agent is Mycobacterium bovis (M. bovis). BTB has a negative impact on the\nproductivity and profitability of livestock farms, reducing production, due to sending\ninfected animals to slaughter, confiscation in slaughterhouses and, because of the\nrestrictions imposed on the commercialization and export of meat and dairy products, and their derivatives. In Argentina, although the National Control and Eradication Program (Law 128/2012, Senasa) reduced its prevalence based on ante-mortem diagnosis in herds and post-mortem epidemiological surveillance in slaughterhouses, due to its complexity, the disease continues to be a challenge. Vaccination, as a\ncomplementary intervention strategy, could reduce the impact of M. bovis infection in cattle, its main host. At present, there are no commercial vaccines, which must be developed in parallel to a differential diagnosis system that allows to distinguish between the vaccinated animal and the naturally infected one, without interfering with the official diagnostic test. In Argentina, the vaccine candidate M. bovis?mce2-phoP, deleted in two independent regions of the genome, the phoP gene (Mb0780) and the mce2AB genes (Mb0604-Mb0605), was obtained. M. bovis?mce2-phoP induced protection against challenge with a virulent strain of M. bovis in the murine model.\nIn order to contribute to the characterization of the M. bovis?mce2-phoP\ncandidate, the general objective of this work was to evaluate the safety and\ntransmissibility of the M. bovis?mce2?phoP strain under experimental and natural infection conditions, and to develop a diagnostic system that allows to differentiate a\nvaccinated animal from an infected one.\nDifferent aspects of the M. bovis?mce2-phoP strain were studied when\ninoculated subcutaneously, such as its safety, its tropism, transmission, excretion, immunological aspects related to the diagnosis of BTB, such as its ability to generate an immune response in intradermal test reaction and gamma interferon release, and its dissemination to the environment. The experimental approach consisted in characterizing these attributes in different experimental animal models and in cattle. In the murine model, the airborne transmission capacity of M. bovis?mce2-phoP was evaluated in a prolonged coexistence assay of BALB/c mice inoculated with the experimental vaccine strain and sentinel mice. Residual virulence was studied in the\nguinea pig model, the laboratory specie most susceptible to infection by M. bovis and that best reproduces tuberculosis, considering the presence of granulomatous lesions in the inoculated animal, possible excretion in feces, and immunological reactivity by intradermal inoculation of tuberculin and recombinant antigens. Finally, in cattle, in a vaccination and infection trial under natural transmission conditions, the protection and safety of the strain was evaluated in inoculated and sentinel animals and for the\nenvironment, potential antigens for ante-mortem differential diagnosis of the vaccinated and infected animal, and post-mortem complementary molecular techniques.\nIn the murine model, the PCR technique demonstrated the presence of M. bovis DNA in tissues of the sentinel mice of the M. bovis?mce2-phoP vaccinated group, although its viability was not verified. Although it retains the ability to replicate in the\nspleen of mice and in lymph nodes of guinea pigs, its attenuation is confirmed by the low bacterial load, the absence of lesions and the survival of all the inoculated animals; compared to that observed with the parental strain. The development of a differential\nPCR allowed us to conclude that, in cattle, neither M. bovis?mce2-phoP DNA nor viability was detected, confirming the findings about its attenuation. In relation to transmissibility,\nno specific genomic sequences were detected in the DNA extracted from stool in guinea pigs and cattle, as well as in soil and drinking water surrounding the cattle under study.\nThese results reinforce those obtained in the murine model and suggest that the vaccine candidate is not excreted, with no potential for transmission to susceptible animals and the environment. Regarding ante-mortem diagnosis in guinea pigs and cattle, the\nrecombinant proteins, PhoP and Mce2B, were used for the first time. Although they\ninduced a certain degree of cell-mediated immune response, they would not be\npromising candidates for the development of a differential diagnosis between natural\ninfection and vaccination, since they induced a response in animals vaccinated with the\nM. bovis?mce2-phoP strain.\nIn conclusion, the attenuation of the M. bovis?mce2-phoP strain in cattle was confirmed, and it was shown that its subcutaneous inoculation does not represent a source of contamination for the environment since it would not be excreted, with no potential for transmission to other susceptible animals or to humans. Although a\ndifferential post-mortem detection tool was developed, more studies are required in relation to the generation of differential diagnosis tools for the live animal. The realization of this work, in addition to deepening the study of key aspects of vaccine candidates such as the protection and safety of a genetically modified organism, strengthened professional skills and multidisciplinary interaction, a strategic link in the optimization of this type of trial. The knowledge generated may be used in the future for purposes like those proposed in this research project.